Victorian horror stories - Stocks, Mike; Chesterman, Adrian Stannard, Lee Brooks, Felicity (Usborne London, 2002)
Six terrifying tales to unsettle and disturb the mind are powerfully retold for today's readers in this collection of classic chillers from the Victorian age